PSXIII-31 Hypothalamic and pituitary responses to resistin in sheep: integration of resistin and leptin signaling involving SOCS-3 and LepRb - Zieba, Dorota A (J Anim Sci, 2019)
Leptin and resistin play important roles in regulating body weight and glucose metabolism. Herein, we hypothesized that resistin is a factor leading to decreased tissue sensitivity to leptin through effects on SOCS-3 and LeptRb expression. Expression of SOCS-3 and LeptRb were determined using Real-Time PCR in selected brain tissues: arcuate nucleus (ARC), ventro- and dorsomedial nuclei (VMH/DMH), preoptic area (POA) and anterior pituitary (AP). Thirty ewes (10/group), ovariectomized with E2-replacement, were fed ad libitum and housed under natural photoperiod. Intravenous treatments consisted of 1) control, 2) low dose of rbresistin (R1; 1.0 μg/kg BW), and 3) high dose of rbresistin (R2; 10.0 μg/kg BW). During long days (LD), LeptRb transcript in ARC decreased in response to R2 (P < 0.001) compared to Control. Expression of LeptRb in VMH/DMH decreased in response to R1(P < 0.001) and R2 (P < 0.001) during short days (SD) and to R2 (P < 0.001) during LD. Conversely, LeptrB transcript increased (P < 0.001) 8-fold in R1 and 4-fold in R2 (P < 0.05) in POA during SD. LeptrB transcript in the AP increased (P < 0.001) 2.1- and 1.8-fold, respectively, in response to R1 and R2 during LD. Within the ARC, SOCS-3 expression increased (P < 0.001) after R2 in LD. In POA, a 2.3-fold (P < 0.001) increase was noted in R2 only during LD. Moreover, SOCS-3 transcript increased in the AP during both LD (8.5-fold) and SD (5.8-fold) in response to R2 (P < 0.001). Evidence indicates that resistin resulted in a consistent decrease in LeptRb (except POA) and increase in SOCS-3 expression during LD in all hypothalamic nuclei. In AP, resistin increased SOCS-3 during both LD and SD and LeptRb transcript during LD. Taken together, the effects of resistin appear to be strongly associated with photoperiod-driven changes in the leptin signaling pathway, which may underlie the phenomenon of leptin resistance.